Pengujian Website Infotech Menggunakan Teknik Black-Box Decision Table - Gita Indah Marthasari; Ani Tri Wahyuningsih; Muhammad Rizky Aviansyah; Muhammad Alfian Ramadhani; Zildan Rahmatullah (Teknik Informatika Universitas Pamulang, 2022)
Infotech is a website-based information system that displays information about practicums, workshops, and information related to the informatics laboratory of the University of Muhammadiyah Malang. Some users complain of system errors such as website server down, login problems, and system bugs. The purpose of this research is to test the quality of the infotech website by using the black-box testing technique of the decision table method. This method focuses on functional testing of software. The main features will be tested, namely the login feature, and the file submit feature. Decision table is a black-box testing technique that contains system test cases in tabular form. Based on the research conducted, the final results show that the two main features tested display output in accordance with predetermined rules or conditions without experiencing system bugs, so it can be concluded that the quality of the infotech website, especially the login and file submission features, is good.